Neandertalczyk i człowiek anatomicznie współczesny w ujęciu najnowszych źródeł archeologicznych i paleoantropologicznych - Dec, Olga (Folia Praehistorica Posnaniensia, 2019)
The article summarises recent discoveries regarding Neandertals and anatomically modern humans (AMH), and tries to examine currently leading trends in the fields of archaeology and palaeoanthropology. Collected evidence suggests that modern research focuses mostly on discussions on the origin of symbolism, cultural and cognitive capacities, and analyses of ancient DNA. Although archaeology and palaeoanthropology undoubtedly provide the highest number of sources, other sciences such as cognitive neuroscience also deliver new, equally valuable perspectives and information.